PERANAN PEREMPUAN DALAM NOVEL MEGAT KARYA RIDA K LIAMSI - Yuke Lestari; Elmustian '; Syafrial ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Justification The study presented is based on the notion that it is the role of women in any major event (Cherce la framme). How the role of women in the novel work Megat Rida K Liamsi. Objectives Seek to describe the role of women. The role of women, we mean here is the task or action of women that occurs in the novel case. This qualitative descriptive study uses the theory of the role of women by Sugihastuti (2000: 113). The study lasted six months, from January to June 2017. Using the documentation with the new Megat source method. The validity of the data using tringulasi and discussion. The results of this study of the role of women as parents dominate the lives of men, followed by a role as a woman. However, the role of privacy of the less important. An interesting discovery in this study of women can benefit men. Successful women are qualitatively more successful than the presence of men. The role of women in general are usually just a housewife, but the authors found the women in the novel Megat Mean worker there as a history teacher and also became a doctorate at Umbai University. The conclusion of this study, in addition to the success of men due to the role of parents (father-mother) but also the roles of men makes women successful. The research data consists of 100 data composed of 6 female characters Each role consists of the role of women as parents, female / domestic, in kinship, in private, in the community, at work. Based on the results of the identification of women's role of each of the female characters that occur in the event that there are women who have a natural role as a man who exceeds kodradnya as a woman found in the novel work Megat Rida K Liamsi. The results of the study recommended to the transmitter, the bookstore, the library manager Riau University, to the researchers who will come.Keywords: The role of women